Aegilops crassa Boiss. repeatome characterized using low-coverage NGS as a source of new FISH markers: Application in phylogenetic studies of the Triticeae - Kroupin, Pavel Yu.; Badaeva, Ekaterina D.; Sokolova, Victoria M.; Chikida, Nadezhda N.; Belousova, Maria Kh.; Surzhikov, Sergei A.; Nikitina, Ekaterina A.; Kocheshkova, Alina A.; Ulyanov, Daniil S.; Ermolaev, Aleksey S.; Khuat, Thi Mai Luong; Razumova, Olga V.; et al. (Frontiers in Plant Science, 2022)
Ae. crassa Boiss. is polyploid grass species growing in the eastern part of the Fertile Crescent, Afghanistan and Middle Asia. It consists of tetraploid (4x) and hexaploid (6x) cytotypes (2n=4x=28, D1D1XcrXcr and 2n=6x=42, D1D1XcrXcrD2D2, respectively) that are similar morphologically. Although many Aegilops species were used in wheat breeding, genetic potential of Ae. crassa was not exploited yet due to uncertain origin and significant genome modifications. Tetraploid Ae. crassa is thought to be the oldest polyploid Aegilops species, which subgenomes can still retain some features of its ancient diploid progenitors. The D1 and D2 subgenomes of Ae. crassa were contributed by Ae. tauschii (2n=2x=14, DD), while the Xcr subgenome donor is still unknown. Owing to ancient origin, Ae. crassa can serve as model for studying genome evolution. Despite of this, Ae. crassa is poorly studied genetically and no genome sequences were available for this species. We performed low-coverage genome sequencing of 4x and 6x cytotypes of Ae. crassa, four Ae. tauschii accessions belonging to different subspecies; diploid wheatgrass Thinopyrum bessarabicum (Jb genome), which is phylogenetically close to D (sub)genome species was taken as an outgroup. Subsequent data analysis using the pipeline RepeatExplorer2 allowed us to characterize the repeatomes of these species and identify several satellite sequences. Some of these sequences are novel, while other are found to be homologous to already known satellite sequences of Triticeae species. The copy number of satellite repeats in genomes of different species and their subgenome (D1 or Xcr) affinity in Ae. crassa were assessed by means of comparative bioinformatic analysis combined with quantitative PCR (qPCR). Fluorescence in situ hybridization (FISH) was performed to map newly identified satellite repeats on chromosomes of common wheat, Triticum aestivum, 4x and 6x Ae. crassa, Ae. tauschii, and Th. bessarabicum. The new FISH markers can be used in phylogenetic analyses of the Triticeae for chromosome identification and the assessment of their subgenome affinities and for evaluation of genome/chromosome constitution of wide hybrids or polyploid species